(untitled) (European Journal of Child Development, Education and Psychopathology, 2019)
After delving into the literature about wellbeing and comprehending the core of preservice teachers’ emotions and human flourishing, we developed a casual-comparative study with students at the Faculty of Educational Sciences (University of Granada). Our research aims to identify the senior students’ beliefs about their teacher training programme in Foreign Languages (English) with reference to the following factors (dependent variables): emotional intelligence; teacher distress; teacher burnout; educational success and; perceived support from family, friends and society. Additionally, our purpose is to unravel whether the attributes variables –such as gender, birthplace, parents’ profession…–indicate statistically significant or not when crossed with the dependent variables. Significant results pointed out that students who decided to join the teaching career with a vocational orientation perceived total support from their close social network. On the contrary, those with a functional reason do not observe any assistance and hence, they are willing to leave the teaching profession sooner. Finally, based on our research findings, we might shed light on improving the teaching experience as well as the upcoming transformations that higher educational systems have to apply in order to meet the real formative needs of pre-service EFL teachers.